Empathy: Critical Analysis and New Research Perspectives - Bovina I.B (Moscow State University of Psychology and Education, 2020)
The purpose of this work is to critically analyze the current state of empathy research as well as to discuss some new lines of research. The relevance of addressing the concept of empathy can be explained in the following manner: if we assume that empathy is associated with helping behavior (some researchers of empathy tend in favor of this interpretation), then in the actual situation associated with the processes of globalization as a whole (interaction with members of other cultures), as well as with a high level of migration processes, researchers are faced with a challenge of finding the factors which promote empathic reactions towards the members of other cultures. On the other hand, the concept of empathy, introduced into psychology in 1909 by E. Titchener, has a rather long history in science, but as far as the literature analysis suggests, researchers differ significantly not only in their understanding and definitions of this phenomenon, or in their explanations tof he mechanisms of empathy, but also in methods of its measurement. Although the possibility of consensus is not considered, however, reflection regarding empathy and methods of its measurement is seen as necessary. This paper outlines some perspectives on empathy research, in particular, in the context of intergroup relations.